2015
DOI: 10.1590/s0102-6720201500040008
|View full text |Cite
|
Sign up to set email alerts
|

Fasting in Elective Surgical Patients: Comparison Among the Time Prescribed, Performed and Recommended on Perioperative Care Protocols

Abstract: Background: Prolonged preoperative fasting may impair nutritional status of the patient and their recovery. In contrast, some studies show that fasting abbreviation can improve the response to trauma and decrease the length of hospital stay.Aim: Investigate whether the prescribed perioperative fasting time and practiced by patients is in compliance with current multimodal protocols and identify the main factors associated. Methods: Cross-sectional study with 65 patients undergoing elective surgery of the diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 29 publications
(38 reference statements)
1
25
0
9
Order By: Relevance
“…The mean times of fasting for solid and liquids prior to a surgery were above the recommended by the ASA () and ERAS protocol (Gustafsson et al, ) in both groups, with approximately 8 hr above the recommended for liquids and 7 hr above the recommended for solids. These observations were similar to studies conducted in other countries (Abebe et al, ; Aguilar‐Nascimento et al, ; Francisco et al, ; Gul et al, ). Thirst in these patients is not only due to the duration of fasting, but can also be influenced by anxiety, medication type and age, for example (Arai et al, ; Conchon et al, ; Leiper, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean times of fasting for solid and liquids prior to a surgery were above the recommended by the ASA () and ERAS protocol (Gustafsson et al, ) in both groups, with approximately 8 hr above the recommended for liquids and 7 hr above the recommended for solids. These observations were similar to studies conducted in other countries (Abebe et al, ; Aguilar‐Nascimento et al, ; Francisco et al, ; Gul et al, ). Thirst in these patients is not only due to the duration of fasting, but can also be influenced by anxiety, medication type and age, for example (Arai et al, ; Conchon et al, ; Leiper, ).…”
Section: Discussionsupporting
confidence: 91%
“…Research on the patients' experience of thirst within hospital settings has found a high prevalence of the symptom in surgical patients, varying from 75% (Aroni, Nascimento, & Fonseca, 2012)-98% (Serato et al, 2019) during the postoperative period, and from 43% (Gul, Andsoy, & Ozkaya, 2018)-69% (Francisco, Batista, & Pena, 2015) during the preoperative period. In the surgical patient, the experience of thirst is particularly unpleasant, with reports that it can give the sensation of suffocation, weakness, irritation, desperation, fear and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative fasting is a regular method to reduce risk of anesthesia in the operation and postoperative complications. Extensive researches at home and abroad have proved that thirst occurs in most patients after operation because of perioperative fasting [3]. Koeppe, A. T. et al [4] reported 12 patients with 10 having undergone laparoscopic surgery think postoperative dry mouth and thirst are hard to bear in the interview.…”
Section: Discussionmentioning
confidence: 99%
“…International protocols indicate a need for a drastic reduction in perioperative fasting and recommend that patients ingest clear liquids up to two hours before surgery, with early reintroduction in the IPP . However, in some health institutions in different countries, compliance with shortened fasting time remains low …”
Section: Perioperative Patient Thirstmentioning
confidence: 99%